Втрати енергії степовими екосистемами за різних видів їх експлуатації та енергетичні основи сукцесійної стабільності степу - Ткаченко, В.С. (Український фітоценологічний збірник, 2007)
Представлены общая характеристика особенностей энергетики степных экосистем и их сравнение с функционально более эффективными структурами, что объясняет гомеостатическое тяготение степей в автогенезе к лигнозной квоте. По литературным данным определялась регуляционная эффективность разных видов эксплуатации степи (выкашивания, выпасания и выжигания). В выводах указана необходимость точного дозирования этих мероприятий в их комплексном использовании для сукцессионной стабилизации степных экосистем. General characteristic of energetic features of steppe ecosystems and comparison them with more functional effective structures, that explain a homeostasis affinity to lignose quota in the spontaneous self-development of steppes, are considered. A regulatory efficience of the different aspects of steppe exploitation (cutting, grazing and fire) are determined by the liferature data. As a conclusion we postulate a necessity of an accurate dosage of such impacts in their complex using for the succesional stabilization of steppe ecosystems.